45 CBTM graduands of joint UMP and AKEPT programme grow leadership talent competency - Sakinah, Abdullah; Mimi Rabita, Abdul Wahit (2022)
KUANTAN, 20 March 2022 - 45 graduands of the joint programme between Universiti Malaysia Pahang (UMP) and Higher Education Leadership Academy (AKEPT) under the Lifelong Learning (LLL) agenda received their diplomas presented by the UMP Vice-Chancellor, Professor Dato’ Ts. Dr. Yuserrie Zainuddin in conjunction with the 15th UMP Convocation Ceremony yesterday.